Effect of Treadmill Exercise on Leak-point pressure and Neuronal Activation in Brain of Rats with Stress Urinary Incontinence - Ko, Il Gyu (Korean Continence Society, 2010)
PURPOSE: Stress urinary incontinence (SUI) commonly occurs in women, and it causes enormous impact on quality of life. Surgery, drugs, and exercise have been recommended for the treatment of this disease. Among these exercise is also known to be effective for relieving thesymptoms of SUI, however, the efficacy and underlying mechanisms of exercise on SUI are poorly understood. In the present study, we investigated the effect of treadmill exercise on abdominal leak-point pressure and neuronal activity in the medial preoptic nucleus (MPA), ventrolateral periaqueductal gray (vlPAG), and pontine micturition center (PMC) following urethrolysis in rats. MATERIALS AND METHODS: Adult female Sprague-Dawley rats, weighing 250±10 g (9 weeks old), were used in this study. After having undergone transabdominal urethrolysis to induce SUI, the rats were divided into three groups (n=6 in each group): a sham operation group, an SUI-induced group, and an SUI-induced and treadmill exercise group. The rats in the exercise group performed treadmill running for 30 min once a day starting 2 weeks after the induction of SUI and continuing for 4 weeks after surgery. For this study, determination of abdominal leak point pressure and immunohistochemistry for c-Fos in the brain were performed. RESULTS: Induction of transabdominal urethrolysis significantly reduced the abdominal leak point pressure, thereby contributing to the induction of SUI. In contrast, abdominal leak point pressure was significantly improved by treadmill exercise. The expression of c-Fosin the MPA, vlPAG, and PMC, the brain areas relating to micturition, was enhanced by the induction of SUI, whereas treadmill exercise significantly suppressed SUI-induced c-Fos expression, suggesting that neuronal activation in the micturition centers was suppressed by treadmill exercise. CONCLUSION: The present results suggest that treadmill exercise may be an effective therapeutic modality for ameliorating the symptoms of SUI.